Contribution of Reading Interest and Guessing Words Meaning in Context Mastery Toward Reading Comprehension - Samsul Amri (J-SHMIC : Journal of English for Academic, 2018)
This study investigates the correlative aspects among three variables; reading interest, guessing words meaning in context mastery, and reading comprehension. It comes up in analyzing the theories and results of some studies that reading interest and guessing words meaning in context mastery would or would not contribute to reading comprehension. It indicates this concern is being confered now on. To achieve this purpose, it is designed as correlational study, where it took the fourth semester students English Study Program of FKIP- Islamic University of Indragiri as sample. Two kinds of instrumentations were utilized; questionnaire and tests. While analyzing the data, the researcher used Pearson Product Moment statistical analysis. Its findings reveal that the correlation coefficient was rxy=0.817, which was categorized as high correlation. Hypothesis testing aslo determined that critical value of rxy was greater than critical value of ttable in significant level 5% (0.817>0.374). It was evidently proven that there was a positive correlation among the students’ reading interest and guessing words meaning in context mastery toward reading comprehension. Then the determination coefficent is 0.667, which means the students’ reading interest and guessing words meaning in context mastery contribute 66.7% toward reading comprehension. It infers that who wants to have better in reading should have better in reading interest and guessing words meaning in contexts mastery.